2022
DOI: 10.1121/10.0013999
|View full text |Cite
|
Sign up to set email alerts
|

Minimal COVID-19 quieting measured in the deep offshore waters of the U.S. Outer Continental Shelf

Abstract: Using a 2-year time series (2019–2020) of 1-min sound pressure level averages from seven sites, the extension of COVID-related quieting documented in coastal soundscapes to deep (approximately 200–900 m) waters off the southeastern United States was assessed. Sites ranged in distance to the continental shelf break and shipping lanes. Sound level decreases in 2020 were observed at sites closest to the shelf break and shipping lanes but were inconsistent with the timing of shipping changes related to a COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It was initially thought that restrictions in place across the globe would lead to a decrease in anthropogenic impacts and, thus far, studies have found dramatic decreases in recreational vessel activity (Pine et al, 2021), large vessel activity (March et al, 2021), sound levels (Derryberry et al, 2020;Thomson and Barclay, 2020), CO 2 emissions (Le Qu er e et al, 2020), and myriad other anthropogenic stressors. However, other studies have found increases in potentially harmful anthropogenic activities, such as use of fishing, sailing, and pleasure craft (Miksis-Olds et al, 2022). When compared alongside the current literature, this study further highlights the need for local assessments of changes in human behavior and impacts on wildlife, which are unlikely to be homogenous across the globe.…”
Section: Discussionmentioning
confidence: 57%
“…It was initially thought that restrictions in place across the globe would lead to a decrease in anthropogenic impacts and, thus far, studies have found dramatic decreases in recreational vessel activity (Pine et al, 2021), large vessel activity (March et al, 2021), sound levels (Derryberry et al, 2020;Thomson and Barclay, 2020), CO 2 emissions (Le Qu er e et al, 2020), and myriad other anthropogenic stressors. However, other studies have found increases in potentially harmful anthropogenic activities, such as use of fishing, sailing, and pleasure craft (Miksis-Olds et al, 2022). When compared alongside the current literature, this study further highlights the need for local assessments of changes in human behavior and impacts on wildlife, which are unlikely to be homogenous across the globe.…”
Section: Discussionmentioning
confidence: 57%